Enhancing energy recovery from corn straw via two-stage anaerobic digestion with stepwise microaerobic hydrogen fermentation and methanogenesis. (20th February 2020) - Fu, Shan-Fei; Liu, Rong; Sun, Wen-Xin; Zhu, Rong; Zou, Hua; Zheng, Yi; Wang, Zhen-Yu
Abstract: Anaerobic digestion (AD) technology attracts increasing concerns for organic waste disposal, renewable energy production as well as organic fertilizer preparation. However, the AD of cellulosic substrate is limited by low efficiency. Microaeration has recently been used to improve the AD efficiency. However, the inhibition of methanogenesis by microaeration limited its application. To enhance the energy recovery from AD of corn straw and avoid the inhibition of microaeration on methanogenesis, two-stage AD including microaerobic hydrogen fermentation (stage I) and methanogenesis (stage II) was investigated. Results showed microaeration had beneficial effects on hydrogen fermentation, methane production and energy recovery depending on the oxygen loading level. At the optimized initial pH of 7.5 for hydrogen production, microaerobic hydrogen fermentation achieved the maximum hydrogen yield of 24.3 mL/g VS (volatile solid, 37 °C and normal pressure) with the oxygen loading of 5 mL/g VS, which was 70% higher than that without microaeration. Overall, the two-stage AD performed better in methane yield and energy recovery than one-stage AD. When the oxygen loading during hydrogen fermentation was 10 mL/g VS of corn straw, the maximum total energy recovery of 10.6 kJ/g VS was obtained, which was 18% higher than that of one-stage AD. The two-stage AD consisting of microaerobic hydrogen fermentation (stage I) and methanogenesis (stage II) is a promising way to enhance the energy recovery from AD of cellulosic substrates like corn straw. Graphical abstract: Image 107252 Highlights: Two-stage AD obtained 5.5% higher overall energy recovery than one-stage AD. Microaeration in hydrogen fermentation further enhanced two-stage AD performance. Suitable microaeration improved AD performance while excess oxygen led inhibition. Microaeration reduced the lag phase length of methane fermentation.